Lipidological competence centres and networks: Future perspectives to improve healthcare of patients with disorders of lipid metabolism. (November 2017) - Heigl, Franz; Pflederer, Tobias; Schettler, Volker; Grützmacher, Peter; Julius, Ulrich; Ringel, Jens; David-Walek, Tilmann; Hettich, Reinhard; Lotz, Norbert; Reeg, Harduin; Graf, Markus; Klör, Hans-Ulrich
Abstract: Background: Numerous healthcare studies have shown that more than 90% of all patients with dyslipidaemia are not treated adequately. Objectives: The "Deutsche Gesellschaft zur Bekämpfung von Fettstoffwechselstörungen und ihren Folgeerkrankungen (DGFF)" [German Society of Lipidology], a non-profit professional membership organization, has already made a series of efforts to improve the care of patients suffering from dyslipidaemia. A recent outcome is the nationwide implementation and certification of Lipidological Competence Centres and Networks (LCCNs). Methods and results: By involving numerous external medical cooperation partners and combining the detailed work of different in-house medical specialists, the Medical Care Centre Kempten-Allgäu was able to improve both the diagnosis and treatment of patients exhibiting disorders of lipid metabolism (DLM). This local lipidological network is so successful, that it may serve as a nationwide standard model for outpatient lipidological care. Detailed organizational structures for improved lipidological care which are suitable to provide a template for future guidelines for the certification of LCCNs have been developed by the Medical Care Centre Kempten-Allgäu. Stringent requirements of implementation with respect to medical staff, content and structure, staff training, patient education and public relations as well as to documentation, quality assurance and quality improvement must be fulfilled both by the lipidological competence centre (LCC) and the cooperation partners within the lipidological network (LN). Finally, members of the health care system (e.g. health policy and health insurances) should be involved in this attempt and convinced of financial support. Conclusion: The implementation and certification of national LCCNs supported by DGFF could contribute to a comprehensive improvement in the care of patients with dyslipidaemia, resulting in prevention of cardiovascular diseases and reduction of cardiovascular sequelae.